Monitoring Soil Salinity and Vegetation Using Multispectral Remote Sensing Data in Interceptor Drain of Salt Marsh in Qazvin Plain - Afshin Uossef Gomrokchi; Mehdi Akbari; Mehdi Akbari; Mahdi Younesi (جغرافیا و پایداری محیط)
Soil salinity and soil salinization as one of the problems facing agriculture and natural resources are of great importance which needs to be prevented with proper knowledge. In this regard, it is important to obtain information about soil salinity and vegetation, such as their amount and distribution. The use of satellite data enables extensive study of soil salinity and vegetation. Since vegetation in most arid and semi-arid regions is strongly influenced by soil properties such as salinity, therefore, this study investigated the effects of Interceptor Drain on soil salinity and vegetation changes using remote sensing capabilities in a 15-year interval. Results showed that construction Interceptor Drain in Salt Marsh Qazvin plain had no effect on soil salinity changes and vegetation cover. According to the results of correlation test between measured soil elements and satellite image bands, bands 5 and 7 were highly correlated with soil SAR (Sodium Adsorption Ratio) index prior to drainage construction and thus, the two bands after drainage construction had a significant correlation with soil EC (Electrical Conductivity) index. In fact, indices including red and infrared bands showed a significant relationship with soil salinity parameters. Also the results of correlation test of remote sensing indices and ground data in the salinity area showed that SI (Salinity Index) index had a highly significant correlation with soil salinity data. Extended Abstract 1-Introduction One of the methods of salinity monitoring is ground-based data, which can be time-consuming and costly, especially if large-scale monitoring is performed over multiple time periods. Using Remote Sensing method and georeferenced and laboratory data, soil salinity changes over time can be monitored. The spectral reflectance of a variety of salts at the soil surface has been studied in several studies which has been used as a direct indicator in remote sensing. However, when the soil moisture is high or the salt layer is not visible at the soil surface or the salt is mixed with other soil components, the direct salinity detection approach will become more complex. However, vegetation and saline-friendly plants can be used as a sign of soil salinity for indirect detection and identification of saline areas based on spectral reflectance of plants. The purpose of the present study was to investigate the trend of soil salinity and vegetation changes using remote sensing capabilities in two intervals before and after construction of Interceptor Drain in Salt Marsh Qazvin plain. Therefore, the trends of soil salinity and vegetation changes over a 15-year period have been studied. 2-Materials and Methods The study area is located in a part of Qazvin province, 150 km northwest of Tehran and the major cities adjacent to the area in Qazvin are Takestan in the west, Abike in the north and Dansfahan in the southwest. Due to the geological conditions of the bedrock and deposition of sediments and groundwater discharge from Qazvin and Hashtgerd Plains, the marsh has been formed which has become saline due to years of severe evaporation. Most saline species have little growth in the salinity range and only in the months when rainfall increases and it is moderately saline, the plants with moderate to low salinity resistance and with a low vegetative period have a short time. Then, with increasing salinity, the soil is seated and dried; only saline-resistant plants in this area survive for the remainder of the year. In this study, spatial and temporal variations of vegetation and soil salinity were investigated using Landsat 7 satellite images. After calculating salinity and vegetation indices, the spatial variability map of soil salinity and vegetation index was prepared. In this study, Landsat satellite images during years 2004 to 2018 were used to study the trends of soil salinity and vegetation changes in Salt Marsh Qazvin plain. After analyzing the remote sensing indices in the study area, the data from satellite images and georeferenced data were compared. The soil salinity and vegetation indices used in the study included 6 soil salinity indices and 5 vegetation indices. The soil samples used in this study were related to 99 observation wells dug in the Proximity of Interceptor Drain of Salt Marsh Qazvin plain during 2010 and 2012. 3-Results and Discussion According to the results of correlation test between measured elements in soil and satellite image bands, bands 5 and 7 were highly correlated with soil SAR index before drainage construction, and thus two bands after drainage construction, with soil EC index. The use of different soil salinity and vegetation index equations gives the results the differential preferences to achieve adequate soil salinity and vegetation index estimation on a large scale using remote sensing data. The evaluation of different soil salinity indices was based on the Statistical test. Statistical test results comparing mean at seasonal variations scale showed that remotely sensed indices related to soil salinity monitoring including BI, SI, SI1, SI2 and SI3 indices showed significant response to seasonal changes in surface soil condition. On the other hand, indices related to monitoring of vegetation status showed a significant difference in vegetation status from spring to summer. The results of correlation test of remote sensing indices and ground data expressed that in the salinity range of SI index there was a significant correlation with soil salinity data. Mean correlation results demonstrated that GVI had a high negative correlation with all salinity indices, but there was less correlation between salinity and other vegetation indices. The satellite images used in this study indicated the highest correlation with soil salinity in the dry months of the year and the correlation between the two factors was reduced in the months with precipitation. Soil salinity estimation based on SI index has been investigated in several cases which revealed that this index is accurate in estimating surface soil salinity in arid and semi-arid regions. 4-Conclusion The present study showed that Interceptor Drain of Salt Marsh Qazvin plain had no effect on soil salinity and vegetation changes in the region, so none of the 11 indices derived from satellite images had significant changes in the period before and after drainage. In other words, soil salinity and percentage of vegetation in the Salt Marsh Qazvin plain have not changed significantly over a period of 15 years. However, due to the dryness of the area and the lack of rainfall as well as the incidence of drought, the fresh water content for natural leaching of adjacent drainage lands is limited and the drainage increases the intensity of groundwater flow and reduces soil salinity by creating a hydraulic gradient. Strengthening of vegetation in the area is affected by drainage. As the Qazvin Plain is one of the agricultural hubs of the country, hence the expansion of saline lands is one of the biggest threats to agriculture in the region. Since deep soil salinity status is one of the important factors in the establishment of vegetation in the region, studies combining remote sensing method, geophysical data and simulation models can lead to a better understanding of the status of the area.